The Journalistic Narratives of the Twitch Patform in the Media - Poveda Criado, Miguel Ángel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Streaming platforms, booming in recent years, have been especially committed to audience participation. Twitch, owned by Amazon, is the benchmark platform for broadcasting eSports. But do the media echo what is happening in the world of electronic sports. At first, the coverage between specialized and general media seems very different, so a comparative analysis between the different information treatments will allow us to draw a conclusion.